Nanomaterials as working electrode material for lithium-ion batteries and sodium-ion batteries - Chua, Zhong Hang (Nanyang Technological University, 2021)
Advancement in electronics devices has led to an increase in demand for energy storage systems. Consequently, a large supply and demand gap has been created particularly in Lithium-Ion Batteries (LIBs) due to the low abundance of lithium. In search of a sustainable source of energy, Sodium-Ion Batteries (NIBs) are considered as a viable replacement to LIBs due to similar electrochemical properties and their high abundance in the Earth’s natural resource. To analyze the electrochemical performance of LIBs and NIBs, potential working electrode materials were studied. In this report, FeS2 was synthesized to function as the active material in the working electrode. The synthesis was conducted via hydrolysis of FeCl3 and mixing the resultant product (β FeOOH) with sulfur powder which was a cheap and easy-to-execute synthesis, yielding a relatively high purity FeS2 particles and electrochemical performance comparable to theoretical hydrothermal synthesized FeS2 particles. The structure and morphology of β-FeOOH and FeS2 particles were studied via X-ray diffraction analysis and Scanning Electron Microscopy (SEM) to analyse their interaction with sulfur powder and interaction with lithium and sodium during discharge-charge cycles respectively. An investigation was also conducted to evaluate the discharge-charge capacity and cycling capability of the different working electrodes in LIBs and NIBs by varying the solvents used in the preparation of the working electrodes.